Executive Function, Eating Behavior, and Preoperative Weight Loss in Bariatric Surgery Candidates: An Observational Study - Walø-Syversen, Gro (Obes Facts, 2019)
BACKGROUND: Individual differences in executive function may influence eating behavior, weight loss (WL), and WL maintenance in obesity treatment. Executive function, which designates top-down cognitive control processes, has been related to eating behaviors which may impact weight, and has been found to be predictive of WL in both behavioral WL programs and after bariatric surgery. Currently, we lack knowledge on the role of executive function in the period before bariatric surgery. If executive function impacts eating behavior and WL in the preoperative period, it may be a target for clinical attention in this stage. OBJECTIVES: We aimed to examine the relationship between objective performance-based measures of executive function, eating patterns, and WL in the preoperative period. METHOD: Baseline data in an ongoing observational longitudinal study of bariatric surgery patients were used. Eighty patients completed neuropsychological testing and self-report questionnaires 4 weeks prior to surgery. RESULTS: We found that working memory predicted WL before surgery and inhibitory control predicted adherence to dietary recommendations. CONCLUSION: Our study indicates that executive function may play a role in short-term WL and dietary adherence prior to surgery, suggesting that executive function in the preoperative period deserves an extended research focus.